A toolbox for parameter-free predictions of solid-state properties of monodisperse glassy polymers with frozen-in molecular orientation - De Focatiis, Davide S.A.; Buckley, C. Paul (Wiley, 2012)
A toolbox that allows designers to predict the properties of oriented glassy polymers using only existing material constants is constructed from a constitutive model applicable to both polymer solids and polymer melts. Two solid-state properties of practical engineering interest are considered: optical birefringence, and craze initiation stress. Predictions from the toolbox are compared to new experimental measurements on well characterized grades of monodisperse polystyrene, and confirm that the toolbox can account for the effect of polymer molecular weight.